Precalculus a graphing approach / Dale Varberg - Varberg, Dale [et. at] (1995)
Numbers, equations, and inequalities, numbers and calculus, order and averages, equations and their graphs, graphs with graphics calculators, inequalities and absolute values, lines, linear regression, review problem se; functions and their graphs, the function concept, linear functions, quadratioc functions, more on graphics calcullators, polynomial functions, rational functions combinations of functions, inverse functions special functions, review problem set; exponential and logarithmic functions, exponents and their properties, functions, logarithms and logarithmic functions, scientific applications, business applications, nonlinear regression, review problem set; trigonometric functions. right triangle trigonometry, general angles and arcs, the sine and cosine functions, graphs of the sine and cosine functions, four more trigonometric functions, inverse trigonometric functions, review problem set; Trigonometric identities, equations, and laws, algebra reviw (optional) basic trigonometic identities, addidition indentities, more identities, trigonometic equations, the law of sines, the law of cosines, vectors, review problem set; sytems of equations and inequalities, inverses of matrices, determinants, systems of inequalities, revieew problem set; analytic geometry, parametric equations, polar coordinates,polar equations of conics, review problem set; sequences, counting, and probability, counting unordered collections,introduction to probability, indepedence in probability problems, chapter 8 review problem set.